2009
DOI: 10.1098/rspb.2009.1765
|View full text |Cite
|
Sign up to set email alerts
|

Grapheme-colour synaesthesia improves detection of embedded shapes, but without pre-attentive ‘pop-out’ of synaesthetic colour

Abstract: For people with synaesthesia letters and numbers may evoke experiences of colour. It has been previously demonstrated that these synaesthetes may be better at detecting a triangle made of 2s among a background of 5s if they perceive 5 and 2 as having different synaesthetic colours. However, other studies using this task (or tasks based on the same principle) have failed to replicate the effect or have suggested alternative explanations of the effect. In this study, we repeat the original study on a larger grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 31 publications
3
64
0
Order By: Relevance
“…This again mirrors arguments that the subjective colours of grapheme-colour synaesthetes arise at a 'cognitive' rather than 'perceptual level' (Gheri et al, 2008;Hupe et al, 2012;Mattingley, 2009;Nijboer et al, 2011;van Leeuwen et al, 2010;Ward et al, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…This again mirrors arguments that the subjective colours of grapheme-colour synaesthetes arise at a 'cognitive' rather than 'perceptual level' (Gheri et al, 2008;Hupe et al, 2012;Mattingley, 2009;Nijboer et al, 2011;van Leeuwen et al, 2010;Ward et al, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…The mere presence of the stimulus (or target) is sufficient to start the process, while awareness of its presence is unnecessary. This can, for example, be tested by looking for pop-out effects in visual search paradigms (Mattingley, 2009;Treisman, 2005;Ward, Jonas, Dienes, & Seth, 2010; though see Mack & Rock, 1998).…”
Section: Automaticity: Defining Featuresmentioning
confidence: 98%
“…Although many take the Gheri et al (2008) and Ward et al (2010) studies to have demonstrated that pre-attentive grapheme-color binding does not occur, we believe this conclusion is premature. The paradigm used for the Gheri et al study was designed only to provide positive evidence that pre-attentive binding does occur; its weakness lies in its inability to demonstrate that pre-attentive binding does not occur.…”
mentioning
confidence: 70%
“…The Ward et al (2010) study also suffers from a significant limitation, as suggested by the authors of the study. The study found that synesthetes who claimed to perceive the majority of graphemes in the array as colored significantly outperformed synesthetes who reported little or no color experience.…”
mentioning
confidence: 94%
See 1 more Smart Citation